Chronic norovirus infection and common variable immunodeficiency. (16th November 2016) - Woodward, J; Gkrania-Klotsas, E; Kumararatne, D
Summary: Chronic infection with norovirus is emerging as a significant risk for patients with immunodeficiency – either primary or secondary to therapeutic immunosuppression. Patients with primary immunodeficiency present a range of pathological responses to norovirus infection. Asymptomatic infections occur and differentiating viral carriage or prolonged viral shedding after self-limiting infection from infection causing protracted diarrhoea can be challenging, due to relatively mild pathological changes that may mimic other causes of diarrhoea in such patients (for instance pathogenic bacteria or parasites or graft- versus -host disease). However, a subset of patients with common variable immunodeficiency (CVID) experience a severe norovirus-associated enteropathy leading to intestinal villous atrophy and malabsorption. Symptomatic infection of up to 8 years has been demonstrated with clinical and histological recovery on viral clearance. Although oral immunoglobulins and nitazoxanide have been used to treat noroviral infections associated with immunosuppression, ribavirin is the only agent to date that has been linked to viral clearance in the Noroviral enteropathy associated with CVID. Graphical Abstract: